SISTEM REKAPITULASI PEMILU STUDI KASUS KOTA PALOPO - MARYAM, FAIZA; PUTRI, PUTRI; MUFLIHA, WILDA NUR (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
General elections, also known as “elections”, are important events in the democratic life of a country. The 2024 general election in Indonesia is considered a critical step that requires increased efficiency and integrity. To process and recap vote data, an electronic system called Sistem Rekapitulasi Suara (SIREKAP) is used. However, there are challenges and risks in using SIREKAP. The purpose of this study is to evaluate the use of the Vote Recapitulation System (SIREKAP) in addressing various issues related to the 2024 General Election. The main focus of this study is on the effectiveness, security, and transparency of SIREKAP amidst the increasing complexity and demands in elections. This research was conducted in a qualitative manner and used a literature study. Data sources include articles, journals, and books related to the research topic. Content analysis was applied to identify patterns, trends and key findings from the data. The results showed that the use of the Vote Recapitulation System (SIREKAP) accelerated the announcement of election results and improved the accuracy of the election process. However, issues such as data security, opacity, and threats to election integrity must be considered. ABSTRAKPemilihan umum, juga dikenal sebagai